Effects of endotoxin exposure on respiratory health among rice mill workers : from workplaces to homes - Shakri, Siti Farhanah Md (2020)
The study of occupational exposure to endotoxin has been broad and high concentration of endotoxins detected across various sectors and industries. These exposure leads to the health effects which include respiratory disorder, asthma, chronic bronchitis and chronic obstructive pulmonary disease. The major route of exposure is through inhalation. In fact, the contamination might be transferred to the family members of the exposed workers. Thus, this comparative cross-sectional study aims to study the workplace to home transmission of endotoxin among rice millers in Malaysia and administrative staffs of USM Health Campus and their respiratory effects. Endotoxin level in inhalable dust for both area and personal samplings were collected using 25 mm Glass Fiber (A) filter loaded in IOM sampler connected to a pump which was clipped at the collar of the rice millers for eight hours. Take-home exposure route was studied by taking the post-shift hands wipes and vacuum home dust from both groups. The questionnaires were circulated among the participants where it consists of six parts; personal details, occupational details, PPE, safety practices at work, respiratory symptoms and take-home exposure. The samples were stored at -20ºC and analysed using Limulus Amoebocyte Lysate (LAL) Chromogenic Endpoint assay at 405 nm. The lung function tests (LFT) were carried out using Spirometer. The results were statistically analysed using SPSS Version 24. Findings for the median concentration of endotoxin for areas and personal inhalable were 0.32 EU/m3 with Interquartile Range (IQR) 0.13 to 0.37 EU/m3 and 0.33EU/m3 with IQR (0.14-0.34) EU/m3 respectively. There was no significant decline in postshifts hand wipes between rice millers and administrative staffs each with the median (IQR); 0.06 (0.00-0.11) EU/ml and 0.04 (0.02-8.37) EU/ml. The administrative staffs have higher detectable of endotoxin in the vacuum home dusts, compared to rice millers with median (IQR); 4.76 (0.16-6.35) EU/ml and 0.21 (0.07-0.21) EU/ml respectively. Most of the rice millers complained having cough (32.4%, n=24), phlegm (27%, n=20) and dyspnoea (16.2%, n=12). Post-shift LFT for FEV1/FVC measured was lower among the rice millers (58.36 ± 21.41) % compared to the administrative staffs (63.65 ± 19.26) %, but was not statistically significant (p = 0.158). However, there were significant correlations between endotoxin concentration and post-shift LFT parameters of measured FVC, FEV1, FEV1/FVC and PEFR (p< 0.05). There was significant difference in home dust endotoxin level between these two groups, but higher detectable endotoxin level found among administrative staffs compared to the rice millers with median (IQR): 4.76 (0.1-6.35) EU/ml and 0.21 (0.07-0.21) EU/ml respectively. This current study has established that the endotoxin level detectable among rice millers in Malaysia was very low which indicating safe level. Despite low level of endotoxin exposure, yet proper protective measure should be applied among the rice millers for long term protection.